SUN CITY - Toft, Anders Høyer (Tidsskriftet Antropologi, 2003)
The main purpose of this article is to enlighten the architectural design process. This is done through the description of how the Danish architect office Møller & Grønborg created a proposal for a new city in the North Western part of China. The city is called Sun City and is planned to be realised within the next 30 years. It is a city the size of Aarhus housing up to 300.000 inhabitants. The article is divided into two parts. Part 1 is the description of the practical creation of the competition entry to the Sun City competition. Part 2 is an attempt to reformulate the understanding of the architectural practice on the basis of how architects actually work (Sun City competition works as a case here) and on the basis of actor-network theory as it is formulated by the French philosopher Bruno Latour.